2002
DOI: 10.1088/0022-3727/35/11/313
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam induced changes in electrical resistivity of polymer films: the case of unplasticized poly(vinyl chloride)

Abstract: Electrical resistivity of the unplasticized poly(vinyl chloride) copolymer (UPVC) films irradiated with high-energy proton beams was studied with reference to a control sample, as a function of both ion energy and ion dose. Upon irradiation with beam energy ranging from 25 up to 37 MeV and at a beam fluence of 0.225×1010 ion cm-2, the room-temperature resistivity of the insulating films decreased by four orders of magnitude from its original value. Furthermore, using 25 MeV proton beams over a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…38 An air drying type of silver paste was applied to the opposite surfaces of polymer samples in a sandwich configuration to ensure good electrical contacts. For the direct current (DC) measurements, a Keithley digital electrometer of the type 6517 A (Keithley, Cleveland, OH, USA) was used for the determination of the DC resistance of the films.…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…38 An air drying type of silver paste was applied to the opposite surfaces of polymer samples in a sandwich configuration to ensure good electrical contacts. For the direct current (DC) measurements, a Keithley digital electrometer of the type 6517 A (Keithley, Cleveland, OH, USA) was used for the determination of the DC resistance of the films.…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…The detailed conductivity behavior of unirradiated samples has been discussed elsewhere [23]. H M AbdelHamid et al, [32] have shown that upon irradiation, room temperature conductivity of the insulating unplasticized poly(vinyl chloride) copolymer (UPVC) films increased by four orders of magnitude from its original value. According to diffusion path model as suggested by Minami 2.8 2.9 3.0 3.1 3.2 3.3 3.4 -3 [33], the conduction mechanism in AgI containing glasses is due to Ag + ion which are attached with I -and not due to those Ag + ions connected to oxygen.…”
Section: Conductivitymentioning
confidence: 99%
“…The increase in r DC may be attributed to the formation of conjugated double bonds [12,15], which promotes the delocalization of charge carriers and hence, the carriers mobility. Also, the irradiation may increase the surface conductivity due to the formation of clusters in the amorphous region within the near surface area of the polymer [11].…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…The principle of this technique is that photons with energies higher than the band gap energy will be absorbed [13,14]. Ion irradiation of polymeric material induces irreversible changes in their macromolecular structure [15]. It can be used to change in a controlled way the physical (e.g.…”
Section: Introductionmentioning
confidence: 99%